Nrf2 signaling contributes to the neuroprotective effect of Cicadidae Periostracum against 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine toxicity (Bangladesh Journal of Pharmacology, 2022)
Cicadidae Periostracum has various pharmacological effects, including neuroprotective potential via nuclear receptor related-1 (NURR1) protein signaling. However, there are no studies on its antioxidative effect. The neuroprotective effect against 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced damage to dopaminergic neurons was evaluated and explored the mechanisms of its antioxidant action, focusing on nuclear factor E2-related factor 2 (Nrf2) in a mouse model of Parkinson's disease. We measured NURR1-related neurotrophic signaling and the levels of antioxidant factors in vitro and in vivo. The effects of Cicadidae Periostracum against MPTP-induced neurotoxicity were associated with inhibition of the neurotrophic signaling pathways and up-regulation of Nrf2 pathways. Thus, Cicadidae Periostracum mitigates neurotoxicity via neurotrophic signaling not only by increasing Nrf2 activity but also by increasing antioxidant activity.